Application of advanced diffusion MRI based tractometry of the visual pathway in glaucoma: a systematic review - Kasa, Loxlan W.; Donovan, Stephanie; Kwon, Eryn; Holdsworth, Samantha; Schierding, William; Danesh-Meyer, Helen (Frontiers in Neuroscience, 2025)
BackgroundGlaucoma is a leading cause of blindness globally, with emerging research suggesting that glaucoma-related degeneration may affect the visual pathway. Recent advancements in magnetic resonance imaging (MRI) offer promising non-invasive methods for evaluating glaucoma, including advanced diffusion MRI (dMRI) and computational techniques. One such technique is tractometry, which quantifies white matter (WM) microstructural properties. While the application of tractometry in glaucomatous patients is developing, several key studies have explored structural changes in the brain, particularly within the visual pathways, in individuals with glaucoma. This systematic review comprehensively evaluates the application of tractometry using advanced dMRI models and techniques to quantify WM in the visual pathway of individuals with glaucoma.MethodsPubMed-Medline and PubMed-Central were screened for articles published until April 11th, 2024. The studies based on patient cohorts affected by primary open-angle glaucoma (POAG), primary angle closure glaucoma (PACG), and normal tension glaucoma (NTG) with the following dMRI techniques and tract-specific analysis approach were included in this review: diffusion tensor imaging (DTI), diffusion kurtosis imaging (DKI), neurite orientation dispersion and density imaging (NODDI), fixel-based analysis (FBA), and dMRI tractometry.ResultsThe selected seven studies incorporate tractometry and advanced diffusion models and techniques (DKI, NODDI and FBA), including DTI. Each study investigated microstructural changes along the visual pathway of glaucomatous patients, finding glaucomatous WM degeneration in the optic nerve (ON), optic tract (OT), and optic radiation (OR), as well as significantly altered WM connections between the brain's visual cortex and non-visual areas. Additionally, tractometric findings correlated with clinical measures of glaucoma, such as intraocular pressure, visual field loss, and retinal nerve fiber layer thickness, indicating the potential that changes in tractometric parameters could provide a complementary marker of the disease.ConclusionsThis review enhances our understanding of WM changes in glaucoma and highlights the potential for dMRI tractometry as a promising tool for early detection and monitoring of the disease. By quantifying WM changes, tractometry offers valuable insights not only into the visual pathway but also into brain regions affected by glaucoma. This could lead to more accurate diagnoses, improved tracking of disease progression, and the development of targeted treatment strategies.